VILLAGE FUND ALLOCATION (ADD) MANAGEMENT IN SUMBERKOLAK VILLAGE, PANARUKAN DISTRICT, SITUBONDO REGENCY - Hasan M Fauzi hasan; Ilmiyah; Vian Affandi (SRODJA (Sroedji Journal Administration), 2026)
Management of Village Fund Allocation in Sumberkolak Village, Panarukan District, Situbondo Regency in 2025. The background of this study is that the management of Village Fund Allocation in Sumberkolak Village as a whole has not been implemented optimally due to problems, namely: lack of transparency in the management of Village Fund Allocation, lack of reliability of the implementing agent for managing Village Fund Allocation, community empowerment programs have not been implemented and lack of supervision from the Village Consultative Body (BPD). This study aims to determine the Management of Village Fund Allocation in Sumberkolak Village, Panarukan District, Situbondo Regency in 2025. This study uses the concept of regional financial management cycle from the Deputy for supervision of regional financial management, 2025. The research method used is the observation method with a qualitative approach. The research data analysis technique uses Miles and Huberman data analysis. The results of the study on the Management of Village Fund Allocation in Sumberkolak Village, Panarukan District, Situbondo Regency in 2025 are that the Management of Village Fund Allocation in Sumberkolak Village, Panarukan District, Situbondo Regency in 2025 is not good. Because planning in Sumberkolak Village lacks community involvement, Village Fund Allocation is prioritized for infrastructure development, community empowerment programs have not been implemented, funds are not disbursed on time, there is a lack of accountability from the Activity Management Team (TPK) in reporting, and there is a lack of oversight from the Village Consultative Body (BPD) and the community. Suggestions include the need for community empowerment activities to ensure community development, empowerment, and independence. Technical guidance on managing Village Fund Allocations, especially in reporting, is needed. Oversight from the BPD should be further enhanced. Keywords: Management; Village Fund Allocation